Aquisição do número gramatical na concordância nominal interna ao DP no português brasileiro - Silva Filho, Jomson Teixeira da (2011)
This research is embedded in the Chomskyan linguistic theory, specifically in the Principles and Parameters framework (Chomsky, 1981 and following) and its more recent reformulations, namely, the Minimalist Program (Chomsky, 1995 and following) and it has as main objectives to analyze and to explain the acquisition process of grammatical number agreement between the elements of the DP in Brazilian Portuguese and to explain the diversity found in the speech data of children with regard to the realization of grammatical number. The acquisition data presented in this investigation are the spontaneous production of two children in the acquisition phase of the city of Maceió-AL, one male and one female, with 2, 11 and 3, 5 respectively. Data from other languages are derived from other studies have made. We hypothesize that the information corresponding to the number on the items that form the functional category Determinant (D) is of fundamental importance for the identification number of the grammatical system of the Portuguese, being the decisive factor responsible for the core agreement between the nominal number of elements of DP in PB. Put another way, the core where the number would be interpretable trace is a parameter to be fixed and the core in determining the number that would be interpretable in BP. This would explain the fact that where agreement is non-redundant, BW brand morphological number appears in the determinant, the other way, ie, one in which the morpheme is adjoined only to the name, an ungrammatical form, at least in PB. This would explain the fact that where agreement is non-redundant, BW brand morphological number appears in the determinant, the other way, i. e, one in which the morpheme is adjoined only to the name, an ungrammatical form, at least in PB. Regarding the agreement between the DP flexionáveis elements, we assume as in Chomsky (1988, 1989) that this is due to a syntactic operation, Agree, but recast in Frampton & Gutmann (2000a). With this reformulation, it is assumed as a sharing agreement between core syntactic features. The results of the analysis of language production of children acquiring the CP, we can conclude that the appearance of determinants can be defined as a trigger for the parameter of agreement nominal internal elements of the DP, the trace of definiteness is crucial for setting the parameter agreement, and the co-occurrence in the speech patterns of children from non-redundant and redundant grammatical and even ungrammatical pattern. We conclude that this fact can be explained due to the variation of the input to which the child is exposed, ie, input variable has also resulted in an output variable. Thinking of PB in the data, we conclude that D is, being the head of the chain-б responsible for definiteness and semantic interpretation at LF, bearing the mark of plural. Where have varieties of brand PB morphology on all elements of the phrase, we can consider that the brand is spreading because of the sharing features.